PROGRAM KEMITRAAN BNN – PKK: KERJA SAMA KOMUNITAS UNTUK PENCEGAHAN PENYALAHGUNAAN NARKOBA DI LINGKUNGAN KELUARGA (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2018)
Drug abuse is a complex issue and causes other health and social problems. This study to understand the community's cooperation to family based drug abuse prevention by describing BNN partnership program with PKK and community based prevention process in Kalideres Subdistrict. The method used was qualitative with descriptive analysis technique. The results showed that BNN's partnership with PKK directly resulted the forming of special cadres of family based drug abuse prevention. The prevention process is community-based through PKK and PKK cadres as agents of social change. Community cooperation for the prevention of drug abuse is done “by and for community